Exploring the Feasibility of Utilizing Limited Gene Panel Circulating Tumor DNA Clearance as a Biomarker in Patients With Locally Advanced Non-Small Cell Lung Cancer - Knapp, Brendan; Mezquita, Laura; Devarakonda, Siddhartha; Aldea, Mihaela; Waqar, Saiama N.; Pepin, Kym; Ward, Jeffrey P.; Botticella, Angela; Howarth, Karen; Knape, Charlene; Morris, Clive; Govindan, Ramaswamy; et al. (Frontiers in Oncology, 2022)
INTRODUCTION: Circulating tumor DNA (ctDNA) testing may identify patients at high risk for recurrence following chemoradiation (CRT) for locally advanced non-small cell lung cancer (LA-NSCLC). We evaluated the feasibility of ctDNA testing on a readily available commercial fixed-gene panel to predict outcomes in patients with LA-NSCLC. METHODS: Plasma of 43 patients was collected at CRT initiation (pre-CRT), completion (post-CRT1), quarterly follow up for 12 months (post-CRT2, 3, 4, 5 respectively) after CRT, and at disease progression. ctDNA analysis was performed using InVisionFirst®-Lung to detect mutations in 36 cancer-related genes. ctDNA clearance was defined as absence of pre-CRT variants at post-CRT1. Patients without detectable pre-CRT variants or no post-CRT1 samples were excluded. RESULTS: Twenty eight of 43 patients (65%) had detectable variants pre-CRT. Nineteen of 43 patients (44%) had detectable pre-CRT variants and post-CRT1 samples and were included in analysis. Median age at diagnosis was 65 years (43-82), and most patients had stage IIIB disease (10/19, 53%). Two patients died from non-cancer related causes before post-CRT2 and were excluded from further analysis. All three patients who did not clear ctDNA had tumor relapse with a median time to relapse of 74 days (30-238), while 50% (7/14) of those who cleared ctDNA have remained disease free. Progression free survival was longer in patients who cleared ctDNA compared to those who did not (median 567 vs 74 d, p = 0.01.) CONCLUSIONS: Although it is feasible to use ctDNA testing on a limited gene panel to identify patients with LA-NSCLC who are at high risk for disease recurrence following CRT, further studies will be necessary to optimize these assays before they can be used to inform clinical care in patients with lung cancer .